Metal-organic frameworks-derived Fe3O4@NC catalyst for selective electrocatalytic reduction of nitrate to dinitrogen - Li, Ruofan; Fan, Jianwei; Zhang, Wei-xian (Chemical engineering journal (Lausanne, Switzerland : 1996), 2025)
Electrocatalytic reduction of nitrate (NO3−-N) to benign nitrogen gas (N2) presents a new solution for sustainable environmental remediation, which requires efficient and stable catalysts. Herein, a metal-organic frameworks-derived catalyst featuring magnetite dispersed on nitrogen-doped carbon (Fe3O4@NC) is reported. Laboratory experiments show that Fe3O4@NC possess competent NO3−-N removal efficiency (63.30 %) and N2 selectivity (96.68 %), while maintaining remarkable stability over 10 consecutive cycles. The Fe(II)/Fe(III) redox cycle within Fe3O4 lattice accelerates efficient electron transfer and enables the dynamic regeneration of active sites. Density functional theory (DFT) calculations further demonstrates that the incorporation of a carbon shell and further N doping facilitates NO3− adsorption, resulting in a more stable adsorption configuration, and lowered the reaction energy barrier of the rate-determining step, leading to a higher reactivity. This work formulates a low-cost noble-metal-free catalyst for nitrate removal and offers insights into rational design of mixed-valence oxides for advanced environmental remediation technologies. [Display omitted] •The Fe3O4@NC catalyst was synthesized with NH2-MIL-88B(Fe) with the precursor.•Fe3O4@NC exhibited superior NO3−-N removal efficiency (63.30 %), N2 selectivity (96.68 %), and stability (10 times).•The incorporated N-doped carbon shell contributed to the enhanced catalytic activity.•The inherent Fe(II)/Fe(III) redox cycle within Fe3O4 promoted electron transfer and enabled active site regeneration.